Nepotisme Konstitusional Dan Prinsip Al-‘Adalah Dalam Fiqih Siyasah: Studi Putusan MK No. 90/PUU/XXI/2023 - Firman Robiansyah; Azzahra Nurrizki Hikmaidha; Mutiah Khanza; Annisa Yulianty (Universitas Islam Negeri Islam Kiai Ageng Muhammad Besari Ponorogo, 2026)
Abstract: This study examines Constitutional Court Decision Number 90/PUU-XXI/2023 regarding the age requirements for presidential and vice-presidential candidates, which sparked widespread controversy due to indications of conflict of interest between the Chief Justice and the decision's beneficiary. The academic concern centers on whether the decision constitutes constitutional nepotism, an analytical category this study constructs by synthesizing political-nepotism theory, political-dynasty studies, and the judicial conflict-of-interest doctrine, and how fiqh siyasah evaluates it. The study employs a normative legal method with juridical-normative, historical, and comparative approaches through library research. The findings indicate that: (a) the Constitutional Court's decision contains procedural and substantive anomalies indicating institutional conflict of interest and satisfies the operational criteria of constitutional nepotism developed in this study; (b) the decision fails to satisfy the four parameters of al-'adālah in fiqh siyasah, namely justice, integrity (al-amānah), deliberation (al-shūrā), and public interest (al-maṣlaḥah al-'āmmah); (c) a reconstruction of check and balances mechanisms grounded in fiqh siyasah values is needed to prevent recurrence of conflicts of interest within constitutional institutions. Keywords: Al-'Adālah; Check and Balances; Constitutional Court Decision; Constitutional Nepotism; Fiqh Siyasah Abstrak: Penelitian ini mengkaji Putusan Mahkamah Konstitusi Nomor 90/PUU-XXI/2023 tentang syarat usia calon presiden dan wakil presiden yang memantik kontroversi luas akibat indikasi konflik kepentingan antara Ketua MK dan benefisiari putusan. Kegelisahan akademis penelitian ini berpusat pada pertanyaan apakah putusan tersebut mengandung nepotisme konstitusional, sebuah kategori analitis yang dibangun penelitian ini melalui sintesis teori nepotisme politik, kajian dinasti politik, dan doktrin konflik kepentingan peradilan, serta bagaimana fiqih siyasah menilainya. Penelitian menggunakan metode hukum normatif dengan pendekatan yuridis-normatif, historis, dan komparatif melalui studi kepustakaan. Temuan penelitian menunjukkan bahwa: (a) putusan MK mengandung anomali prosedural dan substantif yang mengindikasikan konflik kepentingan institusional sekaligus memenuhi kriteria operasional nepotisme konstitusional yang dirumuskan dalam penelitian ini; (b) putusan ini gagal memenuhi empat parameter al-'adālah dalam fiqih siyasah, yakni keadilan, integritas (al-amānah), musyawarah (al-syūrā), dan kemaslahatan umum (al-maṣlaḥah al-'āmmah); (c) diperlukan rekonstruksi mekanisme check and balances berbasis nilai fiqih siyasah untuk mencegah berulangnya konflik kepentingan di lembaga-lembaga konstitusional. Kata Kunci: Al-'Adālah; Check and Balances; Fiqih Siyasah; Nepotisme Konstitusional; Putusan MK